Using PacBio SMRT Sequencing Technology and Metabolomics to Explore the Microbiota-Metabolome Interaction Related to Silage Fermentation of Woody Plant - Du, Zhumei; Sun, Lin; Lin, Yanli; Yang, Fuyu; Cai, Yimin (Frontiers in Microbiology, 2022)
ABSTRACT Silage fermentation is a dynamic process involving the succession of microbial communities and changes in metabolites. Fresh branched and leaves of paper mulberry were used to prepared silage. Crop by-products including corn bran, rice bran, and wheat bran were used as exogenous additives. Pacific Biosciences single-molecule real-time (SMRT) sequencing technology and metabolomics are used to explore the interaction mechanism of microbial structure and metabolites during woody silage fermentation, and verify the principle that exogenous additives can modulate silage fermentation. Under the dual stress of anaerobic and acidic environment of silage fermentation, the microbial community changed from Gram-negative to Gram-positive bacteria, and a large amount of lactic acid and volatile fatty acid were produced, which lowered the pH value and caused the rapid death of aerobic bacteria with thin cell walls. The exogenous additives of corn bran and wheat bran accelerated the dynamic succession of lactic acid bacteria as the dominant microbial community in silage fermentation, increased the metabolic pathways of lactic acid, unsaturated fatty acids, citric acid, L-malic acid and other flavoring agents, and inhibited the growth of Clostridium and Enterobacter, thereby improving the flavor and quality of the silage. However, because rice bran contained butyric acid spore bacteria, it can multiply in an anaerobic environment, led to butyric acid fermentation, and promoted protein degradation and ammonia nitrogen production, thereby reduced the fermentation quality of woody silage. The results showed that during the silage fermentation process, the microbial community and the metabolome can interact, and exogenous additives can affect the fermentation quality of silage. SMRT sequencing technology and untargeted metabolomics revealed the microbiota-metabolome interaction during silage fermentation. Changes in the structure of the microbial community can affect the metabolic pathways, and the final metabolites can inhibit the growth of microorganisms that are not conducive to silage fermentation. Exogenous carbohydrate additives can change the fermentation substrate and affect microbial community structure, thus modulate the silage fermentation.